Prevalence of chronic low back pain: systematic review - Meucci, Rodrigo Dalke; Fassa, Anaclaudia Gastal; Faria, Neice Muller Xavier (Revista de saúde pública, 2015)
OBJECTIVE To estimate worldwide prevalence of chronic low back pain according to age and sex. METHODS We consulted Medline (PubMed), LILACS and EMBASE electronic databases. The search strategy used the following descriptors and combinations: back pain, prevalence, musculoskeletal diseases, chronic musculoskeletal pain, rheumatic, low back pain, musculoskeletal disorders and chronic low back pain. We selected cross-sectional population-based or cohort studies that assessed chronic low back pain as an outcome. We also assessed the quality of the selected studies as well as the chronic low back pain prevalence according to age and sex. RESULTS The review included 28 studies. Based on our qualitative evaluation, around one third of the studies had low scores, mainly due to high non-response rates. Chronic low back pain prevalence was 4.2% in individuals aged between 24 and 39 years old and 19.6% in those aged between 20 and 59. Of nine studies with individuals aged 18 and above, six reported chronic low back pain between 3.9% and 10.2% and three, prevalence between 13.1% and 20.3%. In the Brazilian older population, chronic low back pain prevalence was 25.4%. CONCLUSIONS Chronic low back pain prevalence increases linearly from the third decade of life on, until the 60 years of age, being more prevalent in women. Methodological approaches aiming to reduce high heterogeneity in case definitions of chronic low back pain are essential to consistency and comparative analysis between studies. A standard chronic low back pain definition should include the precise description of the anatomical area, pain duration and limitation level. OBJETIVO Estimar a prevalência mundial de dor lombar crônica, segundo idade e sexo. MÉTODOS Foram consultadas as bases de dados eletrônicas Medline (PubMed), Lilacs e Embase. A estratégia de busca utilizou os seguintes descritores:back pain, prevalence,musculoskeletal diseases,chronic musculoskeletal pain,rheumatic,low back pain,musculoskeletal disorders e chronic low back pain . Foram selecionados os estudos de base populacional de delineamento transversal ou coortes que avaliaram dor lombar crônica como desfecho. A qualidade dos estudos selecionados foi avaliada, assim como a prevalência de dor lombar crônica, segundo idade e sexo. RESULTADOS Foram incluídos 28 estudos nesta revisão. De acordo com a avaliação qualitativa, cerca de um terço dos estudos tiveram pontuação baixa, principalmente em decorrência das altas taxas de não respondentes. A prevalência de dor lombar crônica foi de 4,2% em indivíduos com idade entre 24 e 39 anos e 19,6% entre aqueles de 20 a 59 anos. Dentre nove estudos com indivíduos com 18 anos ou mais, em seis a prevalência de dor lombar crônica variou entre 3,9% a 10,2%, e nos outros três estudos a prevalência foi entre 13,1% e 20,3%. Entre idosos brasileiros, a prevalência de dor lombar crônica foi de 25,4%. CONCLUSÕES A prevalência de dor lombar crônica aumenta linearmente a partir da terceira década de vida até os 60 anos de idade, sendo mais prevalente nas mulheres. Questões metodológicas visando a reduzir a alta heterogeneidade nas definições de casos nos estudos sobre dor lombar crônica são fundamentais para permitir análises comparativas e de consistência entre diferentes estudos. A definição de dor lombar crônica deve incluir a descrição precisa da área anatômica, período de duração da dor e nível de limitação.